Formaldehyde-free adhesive preparation process

Through a preparation process of a realdehyde-free adhesive, using specific materials and process conditions, the problems of formaldehyde in traditional adhesives are solved, and a high-performance and environmentally friendly realdehyde-free adhesive is realized, which improves its performance and application range. .

CN119432260AInactive Publication Date: 2025-02-14NINGBO GREENLEGEND NEW MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411799006.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The presence of harmful substances such as formaldehyde in traditional adhesives, which lead to environmental pollution and human health hazards. At the same time, their performance is insufficient, such as low viscosity, insufficient bonding strength, and poor water resistance, which limits its application range.

Method used

Using a precipitation process of a dextabolite, polyvinyl alcohol, modified starch, acrylate emulsion, nanosilica, initiator and lignin sulfonate are formed by reacting materials such as specific temperatures and stirring conditions. High performance aldehyde-free adhesive.

Benefits of technology

The environmental protection performance and performance improvement of the aldehyde-free adhesive is achieved, the release of formaldehyde is avoided, the viscosity, bond strength and water resistance are improved, the application range is broadened, the preparation process is optimized, the production efficiency and product stability are improved .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432260A_ABST
    Figure CN119432260A_ABST
Patent Text Reader

Abstract

The invention provides a preparation process of a formaldehyde-free adhesive, and relates to the technical field of material science, the preparation process of the formaldehyde-free adhesive completely avoids the use of formaldehyde, eliminates the potential harm of formaldehyde to the environment and human health from the source, and can be used for preparing the formaldehyde-free adhesive by accurately controlling the ratio of the raw materials and reaction conditions and adding specific auxiliaries. The prepared formaldehyde-free adhesive is remarkably improved in the aspects of viscosity, bonding strength, water resistance and other key properties, in the preparation process, parameters such as temperature, stirring speed and reaction time are elaborately optimized, nitrogen is introduced to keep an inert environment of a reaction system, and the formaldehyde-free adhesive is prepared. Side reactions such as oxidation are effectively prevented, and the quality and the stability of the product are improved. The optimized preparation process is simple to operate and easy to control, the production efficiency can be improved, the production cost can be reduced, and large-scale industrial production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material science, and more specifically, particularly relates to a preparation process of a formaldehyde-free adhesive. Background Art

[0002] In modern industry and daily life, adhesives, as an important material, are widely used in many fields such as construction, furniture manufacturing, packaging, printing, etc. However, traditional adhesives often contain harmful substances such as formaldehyde, which will gradually be released during use, causing serious harm to human health and the environment.

[0003] As people's environmental awareness continues to increase and their requirements for quality of life continue to improve, higher requirements are placed on the environmental performance and safety of adhesives. As a widely recognized carcinogen, the problem of formaldehyde in adhesives has received increasing attention. Therefore, the development of a formaldehyde-free adhesive has become an important issue that needs to be urgently addressed in the industry.

[0004] In the past, in order to reduce the formaldehyde content in adhesives, researchers have adopted a variety of methods, such as improving production processes, optimizing raw material formulas, etc., but these methods are often difficult to completely eliminate formaldehyde and may have certain limitations in performance.

[0005] At the same time, traditional adhesives also have some shortcomings in performance, such as insufficient viscosity, insufficient bonding strength, poor water resistance, etc., which to a certain extent limit their application scope and effect.

[0006] In order to meet the market demand for high-performance, environmentally friendly adhesives, researchers are constantly exploring new materials and processes. The application of nanomaterials, high molecular polymers and new additives provides new ideas and possibilities for the research and development of formaldehyde-free adhesives.

[0007] In this context, the present invention proposes a new formaldehyde-free adhesive preparation process, which aims to overcome the defects of traditional adhesives, achieve dual improvements in environmental protection and performance, and provide better quality and safer material solutions for the development of related industries. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a process for preparing a formaldehyde-free adhesive to solve the above problems.

[0009] A process for preparing a formaldehyde-free adhesive comprises the following steps:

[0010] Step A: adding 30 parts by weight of polyvinyl alcohol to 75 parts by weight of deionized water, stirring and dissolving at 90° C. for 35 minutes to obtain solution A;

[0011] Step B: adding 20 parts by weight of modified starch to solution A, stirring and mixing at a temperature of 65° C. for 25 minutes to obtain solution B;

[0012] Step C: 40 parts by weight of acrylic emulsion, 4 parts by weight of nano-silicon dioxide, 1 part by weight of initiator and 5 parts by weight of lignin sulfonate are added to solution B in sequence, and the mixture is stirred and reacted at a temperature of 45° C. for 70 minutes to obtain a formaldehyde-free adhesive, wherein during the stirring reaction, nitrogen is introduced to maintain an inert environment of the reaction system.

[0013] Preferably, the preparation method of the modified starch comprises the following steps:

[0014] S1: 50 parts by weight of native starch and 25 parts by weight of sodium hydroxide solution were mixed, and stirred at 35° C. for 20 minutes to obtain a reaction solution a;

[0015] S2: adding 8 parts by weight of an etherifying agent to the reaction solution a, stirring and reacting at a temperature of 55° C. for 35 minutes to obtain modified starch;

[0016] S3: The modified starch was subjected to ultrasonic treatment for 15 minutes at an ultrasonic frequency of 25 kHz.

[0017] Preferably, the initiator is ammonium persulfate, and its weight portion is 1 part.

[0018] Preferably, in step C, the stirring speed is 350 rpm.

[0019] Preferably, in step C, the pH value of the reaction system is controlled in the range of 7.8-8.2 by adding an acid-base regulator.

[0020] Preferably, the particle size of the nano-silicon dioxide is 30 nanometers.

[0021] Preferably, the solid content of the acrylic emulsion is 45%.

[0022] Preferably, after the reaction in step C is completed, the mixture is naturally cooled to room temperature, and then subjected to microwave irradiation for 10 minutes at a power of 800 W, and then filtered and packaged to obtain a finished formaldehyde-free adhesive.

[0023] Preferably, the degree of polymerization of the polyvinyl alcohol is 1800.

[0024] Preferably, the viscosity of the formaldehyde-free adhesive is 9000 centipoise.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. Excellent environmental performance: The formaldehyde-free adhesive preparation process of the present invention completely avoids the use of formaldehyde, eliminating the potential harm of formaldehyde to the environment and human health from the source. This ensures that the adhesive will not release harmful gases during use, which meets the strict requirements of modern society for environmental protection and health. It not only protects the health of users, but also helps to create a green, pollution-free indoor and working environment. In the fields of building decoration, furniture manufacturing, etc., the use of this formaldehyde-free adhesive can greatly reduce the risk of indoor air pollution and provide people with a safer and more comfortable living and working space. At the same time, for production companies, the use of formaldehyde-free technology can also help enhance the company's environmental image, comply with the strategic direction of sustainable development, and enhance market competitiveness.

[0027] 2. Significantly improved performance: By precisely controlling the ratio of each raw material, reaction conditions and adding specific additives, such as nano-silica, lignin sulfonate, etc., the prepared formaldehyde-free adhesive has been significantly improved in key properties such as viscosity, bonding strength and water resistance. High viscosity ensures that the adhesive can fully adhere to the surface of the adherend during use to form a uniform and firm bonding layer. High bonding strength ensures the reliability and durability of the bond, and can maintain a good bonding effect under both static and dynamic loads. Excellent water resistance allows the adhesive to maintain stable performance in a humid or water environment, broadening its application range, such as in places with high humidity such as kitchens and bathrooms.

[0028] 3. Preparation process optimization: During the preparation process, this process carefully optimized parameters such as temperature, stirring speed, and reaction time. For example, in step A, polyvinyl alcohol was stirred and dissolved at 90°C for 35 minutes to ensure that the polyvinyl alcohol was fully dissolved to form a uniform solution. In steps B and C, reasonable temperature and stirring conditions promoted full mixing and reaction between the components, improved the reaction efficiency and consistency of the product. In addition, the introduction of nitrogen to maintain an inert environment in the reaction system effectively prevented the occurrence of side reactions such as oxidation, and improved the quality and stability of the product. The optimized preparation process is not only simple to operate and easy to control, but also can improve production efficiency, reduce production costs, and is conducive to large-scale industrial production.

[0029] 4. Raw material selection and innovation: Polyvinyl alcohol, modified starch, acrylic emulsion, etc. are selected as the main raw materials, and nano-silicon dioxide and lignin sulfonate are added innovatively. Polyvinyl alcohol provides good film-forming and bonding properties, modified starch increases the cohesion and stability of the adhesive, and acrylic emulsion gives the adhesive excellent flexibility and weather resistance. The introduction of nano-silicon dioxide can improve the strength and wear resistance of the adhesive, and lignin sulfonate helps to improve the dispersibility and compatibility of the adhesive. Through scientific and reasonable raw material combinations and innovative additions, the advantages of each component are fully utilized and the comprehensive performance of the adhesive is synergistically improved.

[0030] 5. Broad application prospects: Since the formaldehyde-free adhesive of the present invention has excellent performance and environmental protection characteristics, its application field is very wide. In the furniture manufacturing industry, it can be used for processes such as splicing and veneering of panels to provide a strong and lasting bonding effect. In the field of building decoration, it is suitable for wallpaper pasting, tile grouting, wooden floor installation, etc., and can meet the bonding requirements of different decoration materials. In addition, it can also be used in packaging, printing, textile and other industries to provide environmentally friendly and high-performance bonding solutions for these industries. As people's requirements for environmental protection and quality continue to increase, this widely applicable formaldehyde-free adhesive will have huge market potential and development prospects.

[0031] 6. Significant economic and social benefits: From an economic perspective, the preparation process of the present invention improves production efficiency, reduces production costs, helps enterprises improve the market competitiveness of products, and increases economic benefits. At the same time, due to the superior performance of the product, it can reduce the rework and maintenance costs caused by adhesive quality problems, saving expenses for users. From the perspective of social benefits, environmentally friendly formaldehyde-free adhesives help promote the green development of related industries, reduce environmental pollution and waste of resources. In addition, its wide application can drive the development of upstream and downstream industries, create more employment opportunities, and promote sustainable economic development and stable social progress.

[0032] 7. High product stability and reliability: By strictly controlling the reaction conditions and adding appropriate additives, the prepared formaldehyde-free adhesive has good stability and reliability. During storage and use, it is not easy to have problems such as stratification, precipitation, and deterioration, ensuring the consistency and stability of product quality. This allows users to use it without worrying about fluctuations in product quality and can safely apply it to various production and construction processes. At the same time, stable and reliable product performance also helps to improve production efficiency and product qualification rate, reducing the risks and losses caused by quality problems.

[0033] 8. Innovative preparation of modified starch: In the preparation of modified starch, unique process steps are adopted, including sodium hydroxide solution treatment, etherification agent reaction and ultrasonic treatment. These steps effectively improve the performance of starch and enhance its compatibility and effect in adhesives. Ultrasonic treatment further optimizes the structure and performance of modified starch, enabling it to better play the role of enhancing bonding performance and improving stability. This innovative preparation method of modified starch provides strong support for the performance improvement of formaldehyde-free adhesives. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0035] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0036] As people pay more and more attention to environmental protection and health, the application of formaldehyde-free adhesives in various fields is becoming more and more extensive. The preparation process of formaldehyde-free adhesive provided by the present invention is intended to meet the market demand for high-performance, environmentally friendly adhesives.

[0037] Embodiment 1:

[0038] Materials preparation:

[0039] Polyvinyl alcohol: 30 g;

[0040] Deionized water: 75 g;

[0041] Modified starch: 20g;

[0042] Acrylate emulsion: 40 g;

[0043] Nano silicon dioxide: 4 g;

[0044] Initiator (ammonium persulfate): 1 g;

[0045] Lignin sulfonate: 5 g;

[0046] Sodium hydroxide solution (for preparing modified starch): 25 g;

[0047] Etherifying agent (for preparing modified starch): 8 g;

[0048] Acid-base regulator (used to adjust pH): appropriate amount.

[0049] Preparation process:

[0050] 30 g of polyvinyl alcohol was added to 75 g of deionized water, and the mixture was stirred and dissolved at 90° C. and 200 rpm for 35 minutes to obtain solution A.

[0051] Add 20 g of modified starch to solution A, and stir and mix at 65° C. and 150 rpm for 25 minutes to obtain solution B;

[0052] 40 g of acrylic emulsion, 4 g of nano-silica, 1 g of initiator and 5 g of lignin sulfonate were added to solution B in sequence, and stirred at 45°C at a stirring speed of 350 rpm for 70 minutes. During the stirring reaction, nitrogen was introduced to maintain an inert environment of the reaction system. The pH value of the reaction system was controlled within the range of 7.8-8.2 by adding an acid-base regulator;

[0053] After the reaction is completed, the mixture is naturally cooled to room temperature, and then subjected to microwave irradiation for 10 minutes at a power of 800 W. The mixture is then filtered and packaged to obtain a finished formaldehyde-free adhesive.

[0054] Viscosity test: measured at 25°C using a rotational viscometer, the viscosity was 8800 centipoise;

[0055] Bond strength test: According to the standard test method, the wood-wood bond strength was tested and the bond strength was measured to be 5.2MPa;

[0056] Water resistance test: The bonded samples were immersed in water for 24 hours and the changes in the bonding surface were observed. No debonding was found.

[0057] Embodiment 2:

[0058] Materials preparation:

[0059] Polyvinyl alcohol: 35 g;

[0060] Deionized water: 87.5 g;

[0061] Modified starch: 25 g;

[0062] Acrylate emulsion: 45 g;

[0063] Nano silicon dioxide: 5 g;

[0064] Initiator (ammonium persulfate): 1.2 g;

[0065] Lignin sulfonate: 6 g;

[0066] Sodium hydroxide solution (for preparing modified starch): 31.25 g;

[0067] Etherifying agent (for preparing modified starch): 10 g;

[0068] Acid-base regulator (used to adjust pH): appropriate amount.

[0069] Preparation process:

[0070] 35 g of polyvinyl alcohol was added to 87.5 g of deionized water, and the mixture was stirred and dissolved at 92° C. at a stirring speed of 220 rpm for 40 minutes to obtain a solution A.

[0071] Add 25 g of modified starch to solution A, and stir and mix at 68° C. and 160 rpm for 30 minutes to obtain solution B;

[0072] 45 g of acrylic emulsion, 5 g of nano-silica, 1.2 g of initiator and 6 g of lignin sulfonate were added to solution B in sequence, and stirred at 48°C at a stirring speed of 380 rpm for 80 minutes. During the stirring reaction, nitrogen was introduced to maintain an inert environment of the reaction system. The pH value of the reaction system was controlled within the range of 8.0-8.2 by adding an acid-base regulator;

[0073] After the reaction is completed, the mixture is naturally cooled to room temperature, and then subjected to microwave irradiation for 12 minutes at a power of 850 W. The mixture is then filtered and packaged to obtain a finished formaldehyde-free adhesive.

[0074] Viscosity test: measured at 25°C using a rotational viscometer, the viscosity was 9500 centipoise;

[0075] Bond strength test: According to the standard test method, the wood-wood bond strength was tested and the bond strength was measured to be 5.8MPa;

[0076] Water resistance test: The bonded samples were immersed in water for 24 hours and the changes in the bonding surface were observed. No debonding was found.

[0077] Embodiment 3:

[0078] Materials preparation:

[0079] Polyvinyl alcohol: 25 g;

[0080] Deionized water: 62.5 g;

[0081] Modified starch: 15 g;

[0082] Acrylate emulsion: 35 g;

[0083] Nano silicon dioxide: 3 g;

[0084] Initiator (ammonium persulfate): 0.8 g;

[0085] Lignin sulfonate: 4 g;

[0086] Sodium hydroxide solution (for preparing modified starch): 18.75 g;

[0087] Etherifying agent (for preparing modified starch): 6 g;

[0088] Acid-base regulator (used to adjust pH): appropriate amount.

[0089] Preparation process:

[0090] 25 g of polyvinyl alcohol was added to 62.5 g of deionized water, and the mixture was stirred and dissolved at 88° C. at a stirring speed of 180 rpm for 30 minutes to obtain a solution A.

[0091] Add 15 g of modified starch to solution A, and stir and mix at 62° C. and 130 rpm for 20 minutes to obtain solution B;

[0092] 35 g of acrylic emulsion, 3 g of nano-silica, 0.8 g of initiator and 4 g of lignin sulfonate were added to solution B in sequence, and stirred at 42°C at a stirring speed of 320 rpm for 60 minutes. During the stirring reaction, nitrogen was introduced to maintain an inert environment of the reaction system. The pH value of the reaction system was controlled within the range of 7.8-8.0 by adding an acid-base regulator;

[0093] After the reaction is completed, the mixture is naturally cooled to room temperature, and then subjected to microwave irradiation for 8 minutes at a power of 750 W. The mixture is then filtered and packaged to obtain a finished formaldehyde-free adhesive.

[0094] Viscosity test: measured using a rotational viscometer at 25°C, the viscosity was 8000 centipoise;

[0095] Bond strength test: According to the standard test method, the wood-wood bond strength was tested and the bond strength was measured to be 4.5MPa;

[0096] Water resistance test: The bonded samples were immersed in water for 24 hours and the changes in the bonding surface were observed. No debonding was found.

[0097] Embodiment 4:

[0098] Materials preparation:

[0099] Polyvinyl alcohol: 40 g;

[0100] Deionized water: 100 g;

[0101] Modified starch: 30 g;

[0102] Acrylate emulsion: 50 g;

[0103] Nano silicon dioxide: 6 g;

[0104] Initiator (ammonium persulfate): 1.5 g;

[0105] Lignin sulfonate: 7 g;

[0106] Sodium hydroxide solution (for preparing modified starch): 37.5 g;

[0107] Etherifying agent (for preparing modified starch): 12 g;

[0108] Acid-base regulator (used to adjust pH): appropriate amount.

[0109] Preparation process:

[0110] 40 g of polyvinyl alcohol was added to 100 g of deionized water, and the mixture was stirred and dissolved at 95° C. at a stirring speed of 250 rpm for 45 minutes to obtain a solution A.

[0111] Add 30 g of modified starch to solution A, and stir and mix at 70° C. and 180 rpm for 35 minutes to obtain solution B;

[0112] 50 g of acrylic emulsion, 6 g of nano-silica, 1.5 g of initiator and 7 g of lignin sulfonate were added to solution B in sequence, and stirred at 50°C at a stirring speed of 400 rpm for 90 minutes. During the stirring reaction, nitrogen was introduced to maintain an inert environment of the reaction system. The pH value of the reaction system was controlled within the range of 8.0-8.5 by adding an acid-base regulator;

[0113] After the reaction is completed, the mixture is naturally cooled to room temperature, and then subjected to microwave irradiation for 15 minutes at a power of 900 W. The mixture is then filtered and packaged to obtain a finished formaldehyde-free adhesive.

[0114] Viscosity test: measured using a rotational viscometer at 25°C, the viscosity was 10,000 centipoise;

[0115] Bond strength test: According to the standard test method, the wood-wood bond strength was tested and the bond strength was measured to be 6.0MPa;

[0116] Water resistance test: The bonded samples were immersed in water for 24 hours and the changes in the bonding surface were observed. No debonding was found.

[0117] In order to more intuitively demonstrate the advantages of the preparation process of the present invention, we compare the above embodiment with the traditional formaldehyde-free adhesive preparation process, and the comparison results are shown in the following table:

[0118] Compare Projects Embodiments of the present invention Traditional crafts Viscosity (cps) 8000-10000 5000-7000 Bond strength (MPa) 4.5-6.0 3.0-4.0 Water resistance All unopened Partial debonding Preparation time (minutes) 210-300 350-450

[0119] It can be seen from the above comparative data that the formaldehyde-free adhesive preparation process of the present invention is superior to the traditional process in terms of performance indicators such as viscosity, bonding strength and water resistance, and the preparation time is relatively short, which has significant advantages.

[0120] Through the above examples and comparative analysis, the preparation process of the formaldehyde-free adhesive of the present invention has the advantages of simple operation, superior performance, environmental protection, etc. By accurately controlling the proportion of each component, reaction conditions and adding special additives, a formaldehyde-free adhesive with high viscosity, high bonding strength and good water resistance was successfully prepared.

[0121] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

Claims

1. A process for preparing a formaldehyde-free adhesive, characterized in that: The following steps are involved: Step A: adding 30 parts by weight of polyvinyl alcohol to 75 parts by weight of deionized water, stirring and dissolving at 90° C. for 35 minutes to obtain solution A; Step B: adding 20 parts by weight of modified starch to solution A, stirring and mixing at a temperature of 65° C. for 25 minutes to obtain solution B; Step C: 40 parts by weight of acrylic emulsion, 4 parts by weight of nano-silicon dioxide, 1 part by weight of initiator and 5 parts by weight of lignin sulfonate are added to solution B in sequence, and the mixture is stirred and reacted at a temperature of 45° C. for 70 minutes to obtain a formaldehyde-free adhesive, wherein during the stirring reaction, nitrogen is introduced to maintain an inert environment of the reaction system.

2. A process for preparing a formaldehyde-free adhesive as claimed in claim 1, characterized in that: The preparation method of the modified starch comprises the following steps: S1: 50 parts by weight of native starch and 25 parts by weight of sodium hydroxide solution were mixed, and stirred at 35° C. for 20 minutes to obtain a reaction solution a; S2: adding 8 parts by weight of an etherifying agent to the reaction solution a, stirring and reacting at a temperature of 55° C. for 35 minutes to obtain modified starch; S3: The modified starch was subjected to ultrasonic treatment for 15 minutes at an ultrasonic frequency of 25 kHz.

3. A process for preparing a formaldehyde-free adhesive as claimed in claim 1, characterized in that: The initiator is ammonium persulfate, and its weight portion is 1 part.

4. A process for preparing a formaldehyde-free adhesive as claimed in claim 1, characterized in that: In step C, the stirring speed was 350 rpm.

5. A process for preparing a formaldehyde-free adhesive as claimed in claim 1, characterized in that: In step C, the pH value of the reaction system is controlled in the range of 7.8-8.2 by adding an acid-base regulator.

6. A process for preparing a formaldehyde-free adhesive as claimed in claim 1, characterized in that: The particle size of the nano silicon dioxide is 30 nanometers.

7. A process for preparing a formaldehyde-free adhesive as claimed in claim 1, characterized in that: The solid content of the acrylic ester emulsion is 45%.

8. A process for preparing a formaldehyde-free adhesive as claimed in claim 1, characterized in that: After the reaction in step C is completed, the mixture is naturally cooled to room temperature, and then subjected to microwave irradiation for 10 minutes at a power of 800 W, and then filtered and packaged to obtain a finished formaldehyde-free adhesive.

9. A process for preparing a formaldehyde-free adhesive as claimed in claim 1, characterized in that: The degree of polymerization of the polyvinyl alcohol is 1800.

10. A process for preparing a formaldehyde-free adhesive as claimed in claim 1, characterized in that: The viscosity of the formaldehyde-free adhesive is 9000 centipoise.

Citation Information

Patent Citations

  • Modified starch for surface sizing of paper, as well as the preparation method and the application of the modified starch

    CN102517991A

  • Novel high-performance industrial glue powder and preparation method thereof

    CN104263282A

  • Rapid board-splicing water-based adhesive

    CN107057609A

  • Method for preparing oxidative in-situ compound water-borne starch-based adhesive

    CN107502230A

  • Preparation method for waterproof starch adhesive for wood

    CN107663430A